Paparan Debu Respirabel Terhadap Kapasitas Vital Paru Pada Pekerja Di Industri Kapur Tohor. - Raudah Alfira Hayati; Zulfikar Ali As; Junaidi Junaidi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2019)
Abstarct: Effect Of Exposure To Respiratory Dust On Lung Vital Capacity In Workers The Limestone Industry. Lime dust is one of the hazardous dust that is dangerous if left exposed. In the airways can cause airway inflammation. This inflammation can lead to obstruction of the airway so that it can reduce lung vital capacity. The purpose of this study was to determine the effect of exposure to respiratory dust on lung vital capacity in workers in the limestone industry in Kelurahan Sungai Ulin ,Kota Banjarbaru. Analytical research design with cross sectional approach. The sample in this study were all workers in the limestone industry. Data analysis used simple linear regression tests. The results of the research statistical tests showed no effect of exposure to respirate dust on the vital capacity of lung workers due to the level of dust that is still below the NAB and the normal lung condition of workers. However, it can be seen the tendency of the problem if high dust levels can reduce lung vital capacity. It is expected that with this study workers will be able to increase awareness about the use of masks when in a work environment.